A combinatorial approach to study the phase constitution of the Ni-Al-Pt system. (1st April 2021) - Cao, G.H.; Zhang, Z.; Li, X.; Skrotzki, W.; Müller, E.; Schneider, R.; Gerthsen, D.
Abstract: Platinum has a beneficial effect on improving alumina scale adhesion and decreasing the alpha alumina growth of aluminide bond coats in thermal barrier coatings. However, complex phases form among Ni, Al and Pt during service due to diffusion between bond coat and underlying Ni-base superalloy substrate. A combinatorial/high-throughput approach to study alloy phase equilibria with precious compositions is high-efficient and cost-saving. The microstructural evolution of a Ni-Al-Pt diffusion triple fabricated by annealing at 1100 ° C for 96 h followed by water-cooling was characterized by transmission electron microscopy and electron probe microanalysis. The high temperature Pt3 Al(h) phase is stabilized due to dissolved Ni, indicating that Ni is a stabilizer for Pt3 Al(h). A ternary phase, Ni2 PtAl, predicted to exist, has been observed experimentally with L12 structure adjacent to (Ni, Pt)3 Al, while the L10 -structured tetragonal NiPt2 Al phase is also confirmed in the Ni-Al-Pt system. Upon cooling, the Ni-rich β-(Ni, Pt)Al undergoes a martensitic transformation from β (B2) to β′-(Ni, Pt)Al (L10 ). The orthorhombic D 2 h 19 -structured (Ni, Pt)5 Al3 phase with lattice parameters a = 0.747 nm, b = 0.682 nm, and c = 0.376 nm was found to form from β′-(Ni, Pt)Al martensite. The orientation relationship of D 2 h 19 and β′ phases is (100)[010] D 2 h 19 // (100)[001] β′. (221) twins are observed in lamellar (Ni, Pt)5 Al3 . Phase constitution is determined in the Ni-Al-Pt system at 1100 ° C. The mechanism of formation of (Ni, Pt)5 Al3 from β′-(Ni, Pt)Al was analyzed. Graphical abstract: Image, graphical abstract